The Utilization of Big Data in University Libraries: A Bibliometric Analysis - Asmaraningsih, Rita; Rahmadanita, Annisa; Hidayat, Enjang (Indonesian Journal of Librarianship, 2024)
Background:The utilization of Big Data is a tangible benefit of technology and interest in analyzing the field has significantly increased in recent years. However, there are limited investigations on the application of the field in university libraries. Objective: This research aimed to identify and describe the characteristics of publications related to Big Data in university libraries using bibliometric analysis to explore and understand the trends. Method: Bibliometric visualization methods were used in the investigation. Results: The results showed that there were 80 publications on Big Data in university libraries from 2014 to 2023. The College of Economics and Management, as well as publications by Ahmad (2019) and Fox Edward, had the most significant influence on the field. Conclusion: The mapping showed the validity of the relationship between theory and the opportunities presented in the field.